Western blotting guru - Najafov, Ayaz; Hoxhaj, Gerta (London, United Kingdom Elsevier/Academic Press, an imprint of Elsevier, 2017)
Western Blotting Guru provides researchers in molecular biology with a handy reference for approaching and solving challenging problems associated with immunoblotting setup and optimization. As a laboratory guide, it emphasizes the technical aspects of efficiently employing immunoblotting as a tool in molecular biology laboratories. The book covers the basic science underlying immunoblotting and detailed description of the method parameters, followed by good benchtop practices, tips and tricks for obtaining high-quality data and a detailed troubleshooting guide addressing a variety of problem types.--Provided by publisher.
Chapter 1 - Introduction -- Chapter 2 - Procedure -- Chapter 3 - Good Practices -- Chapter 4 - Optimization and Troubleshooting -- Chapter 5 - Tips and Tricks -- Chapter 6 - Special Cases -- Chapter 7 - Data Analysis, Storage, Retrieval -- Appendix A - Buffers and Solutions -- Appendix B - SDS–PAGE Gel Tables -- Appendix C - SDS–PAGE Protocol -- Appendix D - Wet Transfer and Immunoblotting Protocol -- Appendix E - Home-Made Enhanced ChemiLuminescence (ECL) Detection -- Appendix F - Stripping Protocols -- Appendix G - Coomassie Staining Protocol -- Appendix H - Lysis of Cells Using Native Conditions -- Appendix H - Lysis of Cells Using Native Conditions -- Appendix I - Quick Denaturing Lysis Protocol -- Appendix J - Protein Tags -- Appendix K - Covalent Crosslinking of Antibodies to Beads -- References
Includes bibliographical references.
Keywords: Western immunoblotting -- Laboratory manuals; Molecular biology; Blotting, Western -- Methods; Electronic books